TRACKING THE SCIENTIFIC LANDSCAPE OF ENVIRONMENTAL IMPACTS ON RESPIRATORY DISORDERS: A BIBLIOMETRIC ANALYSIS - Dr. Tariq Aziz, Yasir Khurshid, Dr. Leena Siddiqui, Dr. Zaid Bux Laghari, Syeda Sobia Shamim Ahmed, Muhammad Talha Shakil (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Respiratory diseases are a specific health issue with considerable involvement ofenvironmental conditions and hazards, including air pollution, weather changes, and workplace exposures in their causation and progression